The Relationship Between Authoritative Parenting Style, Oral Sensory Processing, and Eating Behaviour Related to Picky Eaters among Toddlers in Klang Valley, Malaysia - Kamarudin, Mohd Shah; Hamzaid, Nur Hana; Shahril, Mohd Razif; Haron, Hasnah; Kadar, Masne; Safii, Nik Shanita (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to examine the relationship between authoritative parenting style, oral sensory processing, and eating behaviour related to picky eaters among children aged 3 to 5 years. A cross-sectional study was conducted with 99 mother/father-child dyads from several Klang Valley nurseries and kindergartens. Online survey data collection, including the Child Eating Behaviour Questionnaire (CEBQ), the Child Sensory Profile 2 Questionnaire (CSP-2) (Oral Domain), the Parental Style Dimension Questionnaire (PSDQ), and a demographic questionnaire. Appointment-based collection of anthropometric measurements (weight and height) was conducted. Pearson correlation was used to determine the relationship between eating behaviour (picky eaters), oral sensory processing, and authoritative parenting scores, independent t-test to determine nutrition status and eating behaviour, and chi-square test to examine picky eater status and oral sensory processing classification. Results show that the prevalence of picky eaters is 45.5%. Picky eaters scored low in food responsiveness and food enjoyment but high in satiety response and slowness in eating. There was only an association between picky eating behaviour and oral sensory processing (r=0.22, p=0.003), but no correlation between these indicators and authoritative parenting styles (p>0.05). No significant difference was found in nutrition status between non-picky eaters and picky eaters (p>0.05). According to this study, nearly one out of two children is a picky eater, which is defined by less enjoyment of food, less responsiveness to food, eating slowly, and feeling full quickly. This research is likely to aid in the development of more targeted intervention programmes for picky eaters.